Assessment of levels of navigation systems of medical organizations from the position of lean production - A. A. Kurmangulov; Yu. S. Reshetnikova; N. S. Brynza (Исследования и практика в медицине)
Purpose of the study. To evaluate the level of detail, the amount of visualized data and the levels of navigation systems of primary medical organizations.Materials and methods. The object of this study was 33 primary care medical organizations located on the territory of 7 constituent entities of the Russian Federation. The subject of the study was all the internal and external navigation elements of the MO. The assessment was based on the ALIDS checklist (version 1.0) of 72 indicators, united by five characteristics in general characteristics: architectural-planning and design solutions, transmitted information, levels and navigation elements. The “Levels” block was represented by 19 parameters with a separate assessment of the internal level (9 indicators), the intermediate level (5 indicators) and the external level (5 indicators) of navigation. For each criterion, a nominal dichotomous point score was set with the possibility, if necessary (doubt, clarification, question, etc.) of indicating an expert comment.Results. A full-time study of the navigation systems of 33 primary medical organizations found that the levels of intermediate and external visualization are not used enough. Unlike architectural and planning solutions, various levels of navigation are maximally represented in medical institutions of the Tyumen and Kaliningrad regions, Krasnoyarsk Territory. The lack of an external level of navigation contributes to the main losses of lean production: unnecessary movement, unnecessary transportation and expectations from patients and visitors. Among the objects of internal navigation, cabinets and safety signs are most often placed on the navigation elements. The maximum percentage of compliance among the intermediate navigation category has been established for the main entrances for visitors, including entrances for patients with limited mobility.Conclusion. The navigation system of a medical organization is an important part of the visualization system and one of the criteria for the quality of space. The qualimetry of navigation systems not only of medical organizations, but also of any other buildings and premises, is currently not conclusively presented. Using the author's ALIDS method of audit of navigation systems allows us to give a quantitative and qualitative assessment of the navigation elements used in medical institutions. While improving the navigation systems of existing medical organizations and designing/building new ones, especially with complex mixed or section planning, in order to reduce the main losses of lean manufacturing, it is necessary to create the most detailed and understandable general navigation schemes.